Prognostic Value of Circulating Tumor Cells in Castration Resistant Prostate Cancer: A Meta-analysis - Zheng, Yuxiao; Zhang, Cheng; Wu, Jie; Cheng, Gong; Yang, Haiwei; Hua, Lixin; Wang, Zengjun (Urology Journal, 2016)
Purpose: The prognostic value of circulating tumor cells (CTC) detected in castration-resistant prostate cancer(CRPC) is currently under debate. The aim of our meta-analysis was to evaluate the prognostic effect of CTC andto elucidate whether the detection of CTC in the peripheral blood (PB) of patients diagnosed with CRPC can beused as an independent prognostic factor for survival. Materials and Methods: The Pubmed, Science Citation Index, Cochrane Database, Embase Cell Research databaseand the references in relevant studies were systematically searched. Hazard ratios (HRs) for overall survival(OS) with 95% confidence intervals (CIs), subgroup analysis, sensitivity analysis, meta-regression analysis waspooled and publication bias were conducted. Results: Ten eligible studies enrolling 1206 patients were identified for final analysis. To decrease the heterogeneityof this meta-analysis we excluded two studies after sensitivity analysis. Remained eight studies were enrolledin the pooled analysis and the result revealed that CTC positivity (presence of 5 or more CTCs per 7.5mL PB) wassignificantly associated with a poor OS (HR = 2.76, 95%CI: 2.28-3.34, P < .0001). Conclusion: Our study demonstrated that CTC positivity indicates poor prognosis in patients with CRPC. CTCcounts can be used as an independent prognostic factor of survival rate in patients with CRPC.